The Beast at Heaven's Gate : Georges Bataille and the art of transgression - Hussey, Andrew (Faux titre ;, 2006)
The essays in this collection were originally given at the international colloquium Cent Ans de Bataille: La Bataille de Cent Ans held at the Fondació Tàpies in Barcelona in September 1998. They are written from a variety of perspectives but are drawn together by the singular aim of addressing and interrogating Georges Bataille as our contemporary whose fascination with the rupture between mythical and experimental forms of discourse defines our own age as much as it did in Bataille's own time. More precisely, the essays in this collection range over Bataille's status as a novelist, a poet, an.